Investigating the Experiences of Healthcare Providers in Delivering Maternity Care to Ethnically Diverse Women: A Scoping Review - Jameel, Bismah (My University, 2022)
Background: Women across many ethnicities and backgrounds experience a lower quality of care compared to men, and have reported lower levels of patient satisfaction, and negative health outcomes. Women of various ethnic backgrounds often have health, cultural and religious needs during pregnancy that are not met by their care providers. While addressing patient needs is a priority, providers also face challenges in understanding, accommodating, and addressing women’s needs due to limited understanding of their cultures and available resources in caring for diverse populations. Objective: The purpose of this study is to describe and synthesize information from the literature regarding the perceptions and experiences of healthcare providers in delivering maternity care to ethnically diverse women. Methods: A scoping review was conducted, and database searching occurred in Ovid Medline, Ovid Embase, Ovid Emcare and Web of Science. Primary studies and literature reviews in English were included if they discussed the perspectives of healthcare providers in delivering maternity care to either ethnically diverse women, immigrant women, or a specific ethnic group of women. No time restrictions were placed on articles. Thematic analysis was applied to analyze the data, and results were reported in tabular format. Results: A total of 11 themes were generated across findings, namely, provider-patient communication difficulties, family involvement, lack of health and health system awareness, delays in care, limited time and resources, cultural conflicts, preference for a female provider, creation of stereotypes, prejudice and superior thinking, motivation to help ethnically diverse women, and cultural sensitivity training. Conclusion: Healthcare providers face challenges in addressing the needs of ethnically diverse women, due to resource and time limitations, lack of awareness of cultural norms, and lack of adequate cultural sensitivity training and education. Therefore, there is a need to increase the number of supports for providers as well as improve cultural sensitivity training in medical education.
Healthcare Providers on Culturally Sensitive Maternity Care
Keywords: Maternal Health; Reproductive Health; Cultural Sensitivity; Provider-Patient Relations